Support from Reliance to fight Coronavirus in India - Reliance Industries Limited (2022)
In response to the COVID-19 pandemic, Reliance sets up India’s first exclusive COVID-19 hospital in Mumbai along with BMC. Reliance turns around its manufacturing plants to produce one lakh PPEs and masks daily and embarks on a multi-sortie airlift mission to expedite delivery of PPEs from other countries to India. Reliance has airlifted: • 1 million surgical masks • 3 lakh PPE suits • 3.5 lakh PPE goggles • 3.5 lakh N95 masks • 50,000 isolation gowns Reliance launches COVID-19 testing lab in 2020 to conduct RT-PCR tests and augment India’s testing capacity.